The Semiotics of Built Environment An Introduction to Architectonic Analysis - Preziosi, Donald (Indiana University Press, 1979)
The Semiotics of Built Environment provides an introduction to architectonic analysis, described in the author's preface to the 1979 edition as follows: "This book is concerned with the analysis and description of the built environment as a semiotic system-as a system of meaningful signs. It seeks to establish some of the principal ways in which what will be termed architectonic systems are similar to and different from other forms of human symbolic communication."